2008
DOI: 10.2298/vsp0804286m
|View full text |Cite
|
Sign up to set email alerts
|

Stability investigation of total parenteral nutrition admixture prepared in a hospital pharmacy

Abstract: The results of our study confirmed that a TPN admixture prepared in a hospital pharmacy can be stored without stability loss for at least 60 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It has been shown that a higher concentration and valency of cations cause the destabilisation of the emulsion to a higher extent 21 . There are two kinds of interactions between electrolytes and fat globule surface: non- specific and specific adsorption.…”
Section: Fig 1 -Pareto Chart (Median Of Droplets Size)mentioning
confidence: 99%
“…It has been shown that a higher concentration and valency of cations cause the destabilisation of the emulsion to a higher extent 21 . There are two kinds of interactions between electrolytes and fat globule surface: non- specific and specific adsorption.…”
Section: Fig 1 -Pareto Chart (Median Of Droplets Size)mentioning
confidence: 99%
“…This made IVFEs an important part of total parenteral nutrition regimens 3,4 . This made IVFEs an important part of total parenteral nutrition regimens 3,4 .…”
Section: Introductionmentioning
confidence: 99%